Jerantinine B Enhances the Mitochondria-Mediated Apoptosis by p53 Activation in Human Glioblastoma Cells via a Combination with δ-Tocotrienol - Abubakar, Ibrahim Babangida; Lim, Kuan Hon; Kam, Toh Seok; Loh, Hwei San (Taylor & Francis, 2018)
Combined treatment using tocotrienols at low dosage with chemotherapeutic agents has been suggested as an alternative to circumvent the single high-dose associated metabolic degradation and non-selective toxicity of the bioactive compounds. A synergism of combined δ-tocotrienol and jerantinine B in killing brain cancer (U87MG) cells that could potentially be mediated via mitochondrial and death receptor pathways has been demonstrated previously. Therefore, the present study was conducted to explore the mitochondrial pathway for the apoptosis induction in U87MG cells via the combination of δ-tocotrienol and jerantinine B at low concentrations. Individual δ-tocotrienol and combined (δ-tocotrienol and jerantinine B) treatments induced G0/G1, whereas, IC 50 of jerantinine B induced G2/M cell cycle arrests in U87MG cells. This was mediated via the activation of Bid, Bax and cytochrome c activities. Interestingly, only the individual jerantinine B and combined treatments induced p53 activation. These findings suggest that the combined treatment mediates an apoptosis via the mitochondrial pathway potentiated by p53 activation and may rationalize a better treatment for brain cancer in the future.